2007
DOI: 10.1098/rsbl.2007.0507
|View full text |Cite
|
Sign up to set email alerts
|

Parental aggression against dependent young results in task partitioning in a cooperatively breeding bird

Abstract: In cooperatively breeding species, helpers can alleviate reproductive constraints by assuming the role of primary carers to first-born young, liberating breeders to invest in subsequent broods. However, evidence on how first-born young are transferred to helpers is currently lacking. We propose that breeder–offspring aggression might facilitate inter-brood division and test this idea using data from a wild population of cooperatively breeding pied babblers ( Turdoides bicolor ). After s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Nestlings received the same level of care across group sizes, but adults in larger groups invested less per individual in raising young than adults in smaller groups: they spent less time foraging and more time resting than individuals in smaller groups, and provisioned less biomass to young per individual on average than those in smaller groups. This adds further support to previous evidence that 'load-lightening' occurs in pied babblers (Raihani and Ridley 2008;Ridley and Raihani 2008;Wiley and Ridley 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Nestlings received the same level of care across group sizes, but adults in larger groups invested less per individual in raising young than adults in smaller groups: they spent less time foraging and more time resting than individuals in smaller groups, and provisioned less biomass to young per individual on average than those in smaller groups. This adds further support to previous evidence that 'load-lightening' occurs in pied babblers (Raihani and Ridley 2008;Ridley and Raihani 2008;Wiley and Ridley 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Later, parental aggression appears to cause early-hatched chicks to begin feeding independentlythey do not suffer increased mortality despite receiving less food from the parentsand this frees up parents to shift resources towards the later-hatching chicks. Such parental control behaviours have been reported for other subprecocial water birds such as European coots (Horsfall 1984), moorhens (Leonard et al 1988 parental aggression has been observed in fledgling stages of altricial birds (Leonard et al 1991;Raihani & Ridley 2008), suggesting that some of these parental control dynamics may be widespread in birds. The general pattern here appears to be that the timing of the onset of parental aggression is associated with chick mobility and transition to independence.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, parental aggression has been observed in fledgling stages of altricial birds (Leonard et al . ; Raihani & Ridley ), suggesting that some of these parental control dynamics may be widespread in birds. The general pattern here appears to be that the timing of the onset of parental aggression is associated with chick mobility and transition to independence.…”
Section: Discussionmentioning
confidence: 99%
“…Parents can be aggressive towards dependent young that persistently beg for food (Horsfall 1984), a property that may vary between parents (e.g. Raihani & Ridley 2008); this parental behaviour would be associated with a tendency for low investment in current reproduction. Conversely, parents can also be aggressive towards unrelated adult competitors and predators; in this case, parental aggressiveness directed against non‐family members would be positively associated with the level of investment in current reproduction.…”
Section: Personality In the Context Of Interactions Among Family Membersmentioning
confidence: 99%